PENDIDIKAN GENDER DALAM KERANGKA PENINGKATAN PARTISIPASI PEREMPUAN DI LINGKUNGAN NAGARI (Studi Kualitatif di Nagari Salimpaung Kecamatan Salimpaung Kabupaten Tanah Datar) - Remiswal Remiswal (Program Studi Pendidikan Kependudukan dan Lingkungan Hidup, 2011)
rticipation in nagari environment.This research used qualitative approach, and techniques of observation, interview and document study in collecting data. Data is analyzed through some stages, such as domain analysis, taxonomy, component and theme.The finding of the research shows that nagari environment supports women, women being are still a domestic sphere in Salimpaung nagari, gender education process to woman is learned to encourage domestic roles, and trend to forward potential woman to domestic’s area, and Bundokandung is understanded as self woman and women organization, than woman organization is concentrated its functions. Its impact is to be balance among men’s roles and women’s roles in Salimpaung nagari.Based on those findings, it could be concluded that woman involvement which occurred might be effected by gender education process which received.Therefore, in increasing woman involvement in nagari environment into implementing gender education process by equity and eguality mentioned their quality of roles